Enhancing Teacher Professional Commitment Through Organizational Culture, Self-Efficacy, Job Satisfaction, and Trust in Madrasah Tsanawiyah Negeri Jakarta Selatan - Djuanda, Isep; Sayekti, Siskha Putri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to analyze the influence of organizational culture, self-efficacy, job satisfaction, and trust on the professional commitment of teachers at State Islamic Junior High Schools (Madrasah Tsanawiyah Negeri) in South Jakarta. Methods: This research employed a sequential exploratory mixed-methods design. Data and Sources is Qualitative data were gathered through observations, in-depth interviews, and Focus Group Discussions (FGDs) with teachers and stakeholders. Quantitative data were collected via a questionnaire distributed to a population of 315 teachers. Sampling technique using the Slovin formula with a 5% margin of error, a proportional random sample of 177 teachers from nine madrasahs was selected. Data analysis Techniques; quantitative data were analyzed using Structural Equation Modeling (SEM-PLS) with validity, reliability, and hypothesis testing. The results indicate that self-efficacy (β=0.276, p<0.01), job satisfaction (β=0.312, p<0.01), organizational culture (β=0.228, p<0.05), and trust (β=0.196, p<0.05) significantly and positively affect teachers' professional commitment, with an R² value of 0.684. Strengthening organizational culture, enhancing self-efficacy, ensuring job satisfaction, and fostering trust are critical strategies for sustaining teacher professionalism and improving educational quality.